IMPLEMENTASI DISCOVERY LEARNING BERBASIS ZEPQUIZ UNTUK MENINGKATKAN KEMAMPUAN MENGANALISIS TEKS NARATIF UNTUK MURID KELAS VII C SMPN 6 MADIUN - Fitriana Nur Budiati; Ermi Adriani Meikayanti; Eriana Widya Rahmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Students' understanding of learning materials is not only influenced by how students receive the material, but also by how the teacher presents it. In Indonesian language learning, students still find it difficult to analyze narrative texts, especially in terms of analyzing text and pictures in picture books. This situation causes students to lack concentration and have difficulty identifying story elements, which affects learning outcomes. This study aims to improve the ability to analyze narrative texts that focus on analyzing the emotions of characters in picture books in the VII grade of SMPN 6 Madiun by implementing the Discovery Learning model with the help of the ZepQuiz media. This study uses the Classroom Action Research (CAR) method which is carried out in two sessions. The participants of the study were 30 students in the VII grade of SMPN 6 Madiun with a minimum final criterion (KKM) of 75. Each session consists of a planning stage, action implementation, observation, and reflection. Data collection techniques use student achievement documents and observation sheets. The data are analyzed descriptively, quantitatively, and qualitatively. The results show that the use of discovery learning, based on ZepQuiz, can improve students' analytical skills. The percentage of those who completed traditional learning increased from 13% (4 students) in the pre-primary level with an average grade of 60.53 per class, to 37% (11 students) in the first level with an average grade of 71.53, and reached a maximum of 93% (28 students) in the second level with an average grade of 86.40. These results indicate that this learning model is effective in creating a meaningful and enjoyable deep learning experience for students to achieve narrative reading proficiency.